Development of Group Investigation-Based Mathematics E-Comic to Improve Mathematical Representation Skills of Junior High School Students - Rasilah Rasilah; Yaya S. Kusumah; Dadang Juandi; Dadan Dasari (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
Mathematics plays a fundamental role in developing logical, analytical, and systematic thinking; therefore, mathematics learning should emphasize not only procedural mastery but also meaningful conceptual understanding. One essential process standard in mathematics learning is mathematical representation, as it enables students to organize ideas, communicate reasoning, and transform abstract concepts into visual, verbal, and symbolic forms. In plane geometry, particularly quadrilaterals, many students experience difficulties in drawing accurate figures, linking geometric properties to formulas, and translating contextual problems into mathematical models. In addition to cognitive challenges, affective factors such as low perseverance and the tendency to give up easily indicate the need to strengthen students’ mathematical resilience. This study aimed to develop a group investigation–based mathematics e-comic for quadrilateral topics at the junior high school level and to examine its feasibility and effectiveness. The research employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The product was validated by subject-matter experts and media experts and implemented with 32 seventh-grade students at SMP NU Darul Ma’arif. Data were collected through validation sheets, teacher and student response questionnaires, and learning evaluations. The results indicate that the developed e-comic meets high feasibility criteria and receives positive responses from teachers and students. The integration of narrative visuals with group investigation activities enhances engagement, supports students’ understanding of quadrilateral concepts, and encourages active participation and discussion. Therefore, the proposed e-comic is suitable as an alternative learning medium for junior high school mathematics instruction.